Rhodium‐Catalyzed Mild C7‐Amination of Indolines with Nitrosobenzenes. Issue 47 (18th December 2018) - Xiong, Dan; Wang, Lianhui; Jie, Lianghua; Yang, Zi; Li, Lulin; Cui, Xiuling
Abstract: A mild and practical Rh(III)‐catalyzed C7 –H amination of indolines has been described, which allows the synthesis of a variety of 7‐amino‐substituted indolines with good functional group tolerance and high atom economy. Notably, nitrosobenzenes serve as nitrogen source in this transformation, and therefore behave environmentally friendly for C−N bond constructions. Abstract : An environmentally friendly Rh(III)‐catalyzed C7 –H amination of indolines with nitrosobenzenes has been achieved, which allows the synthesis of a variety of 7‐amino‐substituted indolines with good functional group tolerance and high atom economy.